Adolescent slot machines players: experiences, motivation and cognitive distortions - Ricijaš, Neven (2013)
Slot machines are one of many different types of gaming activities present and available in the Republic of Croatia. Even though the Law on Games of Chance prohibits all gambling activities for minors (persons under the age of 18), professional work with young people, as well as different research clearly shows that minors have access to them. Slot machines are not only present in slot machine clubs and casinos, where minors are not even allowed to enter, but also in different coffee shops making them even more accessible to minors. This study is a part of the scientific project “Habits and Characteristics of Adolescent Gambling in Croatian Urban Areas” conducted on a representative sample of N=1.952 high-school students from 4 major Croatian regional centers (cities of Zagreb, Split, Rijeka and Osijek). Our aim was to explore how often high-school students play slot machines, what is their main motivation for gambling and how they think about games of chance in general. The results show that 25.15% of high-school students played slot machines at least once in their lifetime. Therefore, analysis were conducted on a subsample of N=491 adolescents (M=71.3% ; F=28.7%) with age ranging from 14 to 20 (M=16.76 SD=1.197). The sample was further divided into two groups: (1) those who play slot machines regularly and (2) those who do so occasionally. Participants answered questions about their motivation for gambling, gambling beliefs, their participation in other gaming activities, their experiences of winning money through gambling, as well as about their behavior after they win or lose money. Results suggest that adolescents who play slot machines also play other games of chance and that their more frequent playing is positively correlated with the intensity of other forms of gambling. Students who play slot machines regularly are more motivated by earning money and to become better in gambling. They are also more superstitious and have incorrect beliefs about odds, and also report on gaining large amounts of money and “chasing” These results confirm that minors have access to slot machines, and that playing them regularly has a strong impact on psychological processes and behavioral patterns that can lead to more playing and that make adolescents more vulnerable for developing serious and damaging problems related to gambling.